Everything as a Service: Powering the New Information Economy. - Banerjee, Prith; Bash, Cullen; Friedrich, Rich; Goldsack, Patrick; Huberman, Bernardo A.; Manley, John; Patel, Chandrakant; Ranganathan, Partha; Veitch, Alistair (Computer (00189162), 2011)
The mobility/cloud ecosystem aims to deliver infrastructure, platforms, and software as a service, enabling more people to benefit from ubiquitous information access. The culmination of 10 years' research converges on-demand applications with the infrastructure—servers, storage, networks, and client devices—to support cloud computing.